Análisis para la implementación de un sistema de detección temprana de eventos en la red de accesos de fibra óptica para los servicios de internet y datos para la atención de las incidencias de los clientes gubernamentales en la red de acceso de la Corporación Nacional de Telecomunicaciones EP, de la ciudad de Babahoyo. - Alarcón Guerrero, Javier Arcángel (2021)
Providing timely attention to the service provided by the corporate client is very important, having access to all the information that is required for the attention of the report is essential, the last mile technician must have all the information and resources created to the client for the service provided. The technical supports that follow up the N1 and N2 incidents and the N3 or last mile level support, must work together and without restrictions in each of the processes, they aim to provide a solution to the reported incident, but They must apply quality management to avoid repeatability. Allowing the N3 support to have access to the network resource will allow a better attention to the service, it will prevent the client from falling into disagreement.